The beam diagnostic system at the radiative-technological facility with linear electron accelerator - Sakhno, V.I. (Вопросы атомной науки и техники, 1999)
The main purpose of the production technology is the receiving the materials (production) with specific properties. The radiative technologies belong to the science intensive ones and allow to realize processes, which depend on the exact numerous parameters and ensure the stable production characteristics. The modern radiation technologies engage thin effects of the substance transformation to the manufacture and allow to create unique production.